Den medeltida kroppen. Kroppens och könets ikonografi i nordisk medeltid - Agnes S. Arnórsdóttir (The Royal Danish Library, 2003)
Ágnes S. Arnórsdóttir anmelder "Den medeltida kroppen. Kroppens och könets ikonografi i nordisk medeltid" af Lena Liepe.